The trials of Apollo 1 . The hidden oracle - Riordan, Rick; LeFaiver, Kayley (London Puffin Books, 2016)
"After angering his father Zeus, the god Apollo is cast down from Olympus. He must learn to survive in the modern world until he can somehow find a way to regain Zeus's favor"--
1
Keywords: Apollo -- (Deity); Zeus -- (Greek deity) -- Young adult fiction